Enhancing Mental Health Services Through Digital Communication: Case Study of The KALM Application - Aditia, Rafinita; Yunilisiah, Yunilisiah; Veeraramany, Thayanhithy (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2025)
This study aims to improve digital communication and mental health support through the KALM application by developing more inclusive, user-centered, and psychologically impactful digital mental health services to meet the growing demand for mental health care in urban and rural areas. Using a qualitative approach, literature review and observation methods were applied to collect relevant data from scholarly articles, reports, books, and direct observations of the KALM platform. The findings indicate that KALM has great potential to improve communication between counselors and clients through features such as chat sessions, video calls, and offline counseling. Approximately 80% of users reported feeling more comfortable using this platform compared to face-to-face counseling. The digital campaign #KitaPerluCerita has also been effective in reducing the stigma surrounding mental health and raising public awareness. Additional features like the Gratitude Journal and Well-being Tracker play a significant role in enhancing clients' mental well-being. However, the study identified some challenges, such as internet connectivity issues and counselors' scheduling limitations. The KALM application proves to be effective in providing accessible counseling services and supporting mental health improvement for the Indonesian community, although certain technical issues need to be addressed in the future.